Adopción e implementación del comercio electrónico por empresas medianas en el Perú: un estudio de casos - Yamakawa Tsuja, Peter (2002)
This paper examines the factors associated with the adoption of electronic commerce and the relationship between these factors and the degree of implementation of this technology in medium-sized companies in Peru. It does so base on the empirical evidence provided by companies that represent successful experiences in the use of electronic commerce. Also, in response to the need to use a unit of measurement different from the binary one adopts/does not adopt to establish the degree of implementation of the technology of electronic commerce, this research presents a measurement proposal that considers four dimensions: volume, diversity, amplitude, and depth. The framework of analysis comes from the theory of the diffusion of innovations.